2008
DOI: 10.1111/j.1460-9568.2008.06308.x
|View full text |Cite
|
Sign up to set email alerts
|

GDNF hyperalgesia is mediated by PLCγ, MAPK/ERK, PI3K, CDK5 and Src family kinase signaling and dependent on the IB4‐binding protein versican

Abstract: The function of the isolectin B4 (IB4+)-binding and GDNF-dependent Ret (Ret+)-expressing non-peptidergic subpopulation of nociceptors remain poorly understood. We demonstrate that acute administration of GDNF sensitizes nociceptors and produces mechanical hyperalgesia in the rat. Intrathecal IB4-saporin, a selective toxin for IB4+/Ret+-nociceptors, attenuates GDNF but not NGF hyperalgesia. Conversely, intrathecal antisense to Trk A attenuated NGF but not GDNF hyperalgesia. Intrathecal administration of antisen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
99
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(110 citation statements)
references
References 62 publications
8
99
1
2
Order By: Relevance
“…Consistent with reports of GDNF-induced cutaneous hyperalgesia (Bogen et al 2009;Bogen et al 2008;Ferrari et al 2010;Joseph and Levine 2010), a single intramuscular injection of GDNF produced a robust mechanical hyperalgesia, which lasted for at least 21 days. This hyperalgesia is mediated, at least in part, by nociceptor sensitization, since intramuscular injection of GDNF into the mechanical receptive field of A B C…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Consistent with reports of GDNF-induced cutaneous hyperalgesia (Bogen et al 2009;Bogen et al 2008;Ferrari et al 2010;Joseph and Levine 2010), a single intramuscular injection of GDNF produced a robust mechanical hyperalgesia, which lasted for at least 21 days. This hyperalgesia is mediated, at least in part, by nociceptor sensitization, since intramuscular injection of GDNF into the mechanical receptive field of A B C…”
Section: Discussionsupporting
confidence: 85%
“…While cutaneous GDNF-induced hyperalgesia is a wellestablished phenomenon Bogen et al 2008Bogen et al , 2009Ferrari et al 2010;Joseph and Levine 2010) and high levels of GDNF have been reported in painful neuromuscular diseases, studies of the role of GDNF in skeletal muscle nociception are lacking. The results of the present study indicate that GDNF produces a long-lasting muscle hyperalgesia mediated by action at IB4(ϩ) nociceptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also reported in an in vivo experiment that hyperalgesia by GDNF involved versican (Bogen et al 2008). The latter authors speculated that glycosaminoglycan side chains of versican might interact with GDNF or soluble GFRα1 secreted by surrounding tissue, causing intracellular signal transduction via PLCγ and kinases mentioned above.…”
Section: Discussionmentioning
confidence: 90%
“…neurones Bogen et al 2008). To clarify any involvement of these intracellular signalling mechanisms in the low pH-induced sensitization, we examined the effects of a strong and broad-spectrum kinase inhibitor, staurosporine, and a phospholipase C inhibitor, U73122.…”
Section: Absence Of Contribution Of Intracellular Kinase and Phospholmentioning
confidence: 99%